Pengaruh Aplikasi Pupuk Kandang Sapi dan Pupuk NPK 16:16:16 Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum L. ) - Kasyfillah Faqh, Moh; Furoidah, Nanik (JURNAL AGROPLANT, 2024)
This study aims to determine the main effect of manure and the combination of cow manure and NPK 16:16:16 on the growth and yield of tomato plants. This research was conducted in Kemiri Village, Panti District, Jember Regency with an altitude of 306 meters above sea level. The research was conducted from May to July 2023. This research used a Randomized Completely Block Design (RCBD) with a single factor, consisting of six levels of treatment and four times replication. Observational data were analysed using ANOVA test, if there is a significant difference, then continued with the Least Significant Difference (BNT) test at the 5% level using Microsoft Excel. The results showed that the combination treatment of 400 g cow manure + 10 g NPK 16:16:16 fertilizer (P3) showed significantly different in the parameters of plant height, number of leaves, and flower appearance. The combination of 400 g cow manure + 20 g NPK 16:16:16 fertilizer (P5) showed significantly different in the treatment of stem diameter. The combination of 400 g cow manure + 15 g NPK 16:16:16 fertilizer (P4) showed a significant difference in the number of fruits per plant. While the single treatment of cow manure (P1) did not show a significantly different effect on all parameters.